2023
DOI: 10.7759/cureus.36139
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Education in Saudi Arabia: Barriers and Solutions From a Cross-Sectional Survey Study

Abstract: Occupational therapy (OT) is an important healthcare profession in Saudi Arabia (SA). Yet, no studies have explored the status of OT education in SA. The current study aims to investigate the status of OT education in SA, as well as the barriers and solutions. MethodsA cross-sectional-based survey was conducted. Institutions that offered OT programs were identified and an electronic survey was sent to OT program directors across SA that agreed to participate. The survey included items that focused on the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 16 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Low-medium quality DISCERN and JAMA scores and difficult readability have been reported in studies on different subjects, similar to our study. [35,38–41] However, in our study, among the artificial intelligence chat robots, perplexity especially attracts attention with its high DISCERN and JAMA scores. The fact that the answers of this artificial intelligence chatbot contain references has caused its DISCERN and JAMA scores to be high.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Low-medium quality DISCERN and JAMA scores and difficult readability have been reported in studies on different subjects, similar to our study. [35,38–41] However, in our study, among the artificial intelligence chat robots, perplexity especially attracts attention with its high DISCERN and JAMA scores. The fact that the answers of this artificial intelligence chatbot contain references has caused its DISCERN and JAMA scores to be high.…”
Section: Discussionmentioning
confidence: 78%
“…Researchers also specifically stated that 11.5% of the 104 questions asked to ChatGPT were answered incorrectly. [34] Golan et al [35] assessed the quality of online content on shock wave therapy for erectile dysfunction, and found that ChatGPT’s performance in assessing the quality of text content was inadequate and was not consistent with standards set by human evaluators and reliable tools. [35] Momenaei et al [36] evaluated the relevance and readability of the medical information provided by ChatGPT-4 regarding common vitreoretinal surgeries for retinal detachments (RDs), macular holes (MHs), and epiretinal membranes (ERMs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, ChatGPT scored poorly when compared to human reviewers using the DISCERN tool in identifying poor-quality information regarding shock wave therapy for erectile dysfunction. 3…”
mentioning
confidence: 99%